(untitled) (Prithvi Journal of Research and Innovation, 2023)
This study evaluates the alignment of teacher education (TE) programs of Tribhuvan University (TU) with the teacher selection courses of Teacher Service Commission (TSC), using a comparative, exploratory-cum-explanatory research design. The data collection methods included content analysis, focus groups, and interviews. The data analysis method includes interpreted phenomenological analysis (IPA). The results showed a lack of course compatibility, with only 9% of the teacher license (TL) and teacher selection (TS) courses from the Teacher Service Commission (TSC) and Tribhuvan University (TU) being comparable. The study also questions the relevance of current TE, TL, and TS programs, particularly in incorporating professional skills and TE innovations for classroom instruction. To improve TE, respondents proposed strategies such as introducing digital pedagogy, combining pedagogical and general education subjects, updating subject-specific content, and adding practical skills for responsive teaching. The study concluded that closing the theory-practice gap in teacher education is challenging and calls for various changes, institutional cooperation, and teamwork. Similarly, the policymaking and implementing agencies of education are suggested to consider course reviews, required training for teaching professionals, sufficient internships for pre-service teachers, the use of TE’s innovations and professional skills, improvements to the teacher selection process, and collaboration among education stakeholders.